Is the trade union still necessary in the contemporary society? - Zhang, Xiaomin (2018)
For over two centuries since the eighteenth century, the trade union has always been considered as the democratic organisation. They occupied the central stage in the world history working as a representative agency to safeguard employee rights from been violated. The trade union does not only play a role in the workplace but also produce their influence in the society at large. However, the trade union has undergone a tremendous change since the 1980s whereby they are facing the loss of their membership, power as well as influence. The retreating status of the trade union has formed the central debate of the necessity of the trade union in the contemporary society among scholars. This study, therefore, tried to contribute a new perspective into the debate, which is the importance of the trade union in the regulation of employment relationship. The industrial disruption occurred between the British universities and the University and College Union in 2018, which has been considered the largest industrial disruption that existed in the history of the British higher education industries. This also provided another motivation and the material for the study. Based on the case study of the UCU strike, the central argument of the study is that the trade union is still necessary in the contemporary society due to the irremovable conflict and power imbalance featured in the employment relationships. The study elucidated why the trade union is still necessary in the contemporary society from the perspectives of interest representation, union power and collective bargaining. These roles and functions of the trade union played in the regulation of employment relationship were highlighted. Moreover, the study also critically pointed out why the necessity of the trade union still remains doubtful in the contemporary society by demonstrating the challenges they are facing nowadays, which mainly focused on the perspectives of diverse contemporary workforce and the reducing support from the government and employers.